2017
DOI: 10.1007/978-3-319-66188-9_13
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Opportunistic Ambient Notifications in the Smart Home to Enhance Quality of Live

Abstract: Smart home technology became more and more widespread within recent years. They aim to make life easier and taking over unwanted tasks. In traditional homes, it is often not clear whether all windows and doors of a house are closed before inhabitants leave the home or go to sleep. However, this can be easily addressed by smart homes. We present a system based on opportunistically located ambient lights that assist inhabitants of a smart home in answering this question. In this paper, we show the concept of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In the home environment this can occur in the evening and night while the inhabitants are watching TV if an ambient light is placed nearby. This problem for example had to be dealt with in the work by Seiderer et al [34] and could be observed for an ambient screen by Consolvo and Towle in [14]. The same issue occurs in the meeting room during presentations using the projector in the evening or when the room has to be darkened with the indoor and / or outdoor shutters.…”
Section: Ambient Light In the Office Environmentmentioning
confidence: 99%
“…In the home environment this can occur in the evening and night while the inhabitants are watching TV if an ambient light is placed nearby. This problem for example had to be dealt with in the work by Seiderer et al [34] and could be observed for an ambient screen by Consolvo and Towle in [14]. The same issue occurs in the meeting room during presentations using the projector in the evening or when the room has to be darkened with the indoor and / or outdoor shutters.…”
Section: Ambient Light In the Office Environmentmentioning
confidence: 99%
“…It makes sense to irrigate plants automatically when inhabitants are not at home for a long time and certainly contributes to the peace of mind [6]. However, it should not be the goal of domestic technology to replace the experiences from daily habits and routines that inhabitants enjoy but enhance those home experiences with technology [19,39]. The daily routine of watering plants belongs to such experiences because it includes not only watering but also caring for the plants in the context of human social behavior.…”
Section: Design Approaches For Interaction With/in Smarthomesmentioning
confidence: 99%
“…Recent developments in computing and design propagate designs for well-being (e.g., [7,15,37]), mindfulness (e.g., [3,47]), (soma)esthetic appreciation [21], mental and physical health (e.g., [9,13,35]). To this end, researcher build on foundations and advances in affective computing and user experience research and take inspirations from emerging (interdisciplinary) fields, such as positive computing [10], somaesthetics [38], and mindfulness based stress reduction (MBSR) [23].…”
Section: Somaesthetics In Hci Positive Computingmentioning
confidence: 99%